2017
DOI: 10.18178/joaat.4.2.196-199
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Broiler Farmer in Partnerships System at Surakarta, Indonesia

Abstract: The research was conducted to evaluate the performance of broiler chicken farmer with partnership system. The research was conducted using survey method to broiler chicken farmer who joining partnership system. Descriptive explanative method was using to analyze data. This research used descriptive explanatory method using a quantitative approach. The result showed that income of the broiler farmer received from the core-breeder Rp 13,836,594.08 /head/ period, while net-income of the famers is amounted to Rp 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 3 publications
0
12
0
3
Order By: Relevance
“…In the current economic climate there is strong competition between livestock production companies, with little incentive to reduce antimicrobial use, particularly as it may be associated with significant economic losses for the private sector [34,51,52]. The study results revealed that contract farmers more frequently identified an economic advantage to using antimicrobials when compared with independent farmers.…”
Section: Economic Drivers Of Antimicrobial Usementioning
confidence: 99%
See 2 more Smart Citations
“…In the current economic climate there is strong competition between livestock production companies, with little incentive to reduce antimicrobial use, particularly as it may be associated with significant economic losses for the private sector [34,51,52]. The study results revealed that contract farmers more frequently identified an economic advantage to using antimicrobials when compared with independent farmers.…”
Section: Economic Drivers Of Antimicrobial Usementioning
confidence: 99%
“…It has been reported that such an approach minimises the risk of high production costs in the face of a declining market and offers a more secure income for farmers [33]. Typically, in these contract agreements the contractor provides day old chicks (DOCs), feed, antimicrobials, vaccines, technical advice and product marketing while the farmers provide the housing and labour [34]. There were substantial differences in farm type between the provinces with 78% and 97% of farms in Lampung and Central Java province being contract farms respectively, in comparison to only 28% in West Kalimantan province.…”
Section: Respondent and Farm Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of feed conversion ratio usually occurs because the feed is provided by unofficial companies, wrong in the use of technology, careless in maintenance, cleanliness and stable, lack of knowledge about feed standards, or feeding too much [5]. The average farmer earns a profit that when compared to the Minimum Wage Regional (UMR) in the research area gained profits are quite satisfactory [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Majid and Hasan's (2014) study discussed the variable mostly affecting the price of poultry, viewed from some indicators. Meanwhile, Nurtini et al, (2017) studied the harvest product and productivity obtained by broiler cattle breeder with partnership system. Considering this fact, this article aims to discuss social exchange in broiler partnership business with core-plasma partnership system.…”
Section: Introductionmentioning
confidence: 99%